Resprouting and mortality of juvenile eucalypts in an Australian savanna: impacts of fire season and annual sorghum - Werner, Patricia A; Franklin, Donald C (Australian journal of botany, 2010)
In northern Australian savannas, canopy tree species often have juvenile tree banks that are composed mainly of small individuals of indeterminate age that have resprouted repeatedly after fire. Little is known about their demography. We report the initial responses (mortality, topkill and resprouting type) of 3133 marked juvenile eucalypts to set fires of different seasons (early dry season, late dry season, wet season, unburnt) in a 32400m² field experiment. Fire treatments were repeated in plots dominated by a native annual grass (sorghum) that becomes senescent before the early dry season and provides the main fuel of savanna fires, and in others with little or no sorghum, but instead other native grasses and forbs that remain green well into the dry season. Most juvenile eucalypts 22% in the low-intensity early dry season fire in plots with little or no annual sorghum, compared with <2% in all other fire/understorey combinations. We suggest results are related to fire behaviour, seasonal carbohydrate storage dynamics and competition with ground-layer plants.